1999
DOI: 10.1046/j.1462-2920.1999.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic utilization of alkylbenzenes and n‐alkanes from crude oil in an enrichment culture of denitrifying bacteria affiliating with the β‐subclass of Proteobacteria

Abstract: Denitrifying bacteria were enriched from freshwater sediment with added nitrate as electron acceptor and crude oil as the only source of organic substrates. The enrichment cultures were used as laboratory model systems for studying the degradative potential of denitrifying bacteria with respect to crude oil constituents, and the phylogenetic affiliation of denitrifiers that are selectively enriched with crude oil. The enrichment culture exhibited two distinct growth phases. During the first phase, bacteria gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 51 publications
3
45
0
1
Order By: Relevance
“…It is expected that cyclohexane volatilizes easily in oxic environments at the air, whereas it may tend to persist in 'closed' anoxic environments. While straight-chain saturated and aromatic petroleum hydrocarbons under anoxic conditions in the presence of nitrate often promote enrichment of Betaproteobacteria (Rabus et al, 1999;Ehrenreich et al, 2000;Widdel et al, 2009), the presently obtained enrichment with cyclohexane and nitrate was dominated by a deltaproteobacterium. Growth of this bacterium, the likely degrader of cyclohexane, was accompanied by a member of the Planctomycetales, which was apparently responsible for scavenging nitrite by anaerobic ammonium oxidation (Musat, 2005).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It is expected that cyclohexane volatilizes easily in oxic environments at the air, whereas it may tend to persist in 'closed' anoxic environments. While straight-chain saturated and aromatic petroleum hydrocarbons under anoxic conditions in the presence of nitrate often promote enrichment of Betaproteobacteria (Rabus et al, 1999;Ehrenreich et al, 2000;Widdel et al, 2009), the presently obtained enrichment with cyclohexane and nitrate was dominated by a deltaproteobacterium. Growth of this bacterium, the likely degrader of cyclohexane, was accompanied by a member of the Planctomycetales, which was apparently responsible for scavenging nitrite by anaerobic ammonium oxidation (Musat, 2005).…”
mentioning
confidence: 89%
“…Enrichments with hydrocarbons (n-alkanes, alkylbenzenes) and nitrate very often selected true denitrifiers (viz. that reduce NO 3 À to N 2 ) of the Betaproteobacteria (for example, Rabus et al, 1999;Ehrenreich et al, 2000). Physiological and genomic Anaerobic cyclohexane degradation and anammox F Musat et al studies (Lovley and Phillips, 1988; http://img.jgi.…”
Section: Phylotypes In the Enrichment Culturementioning
confidence: 99%
“…Anaerobic alkane activation mechanism differs completely from that of aerobic alkane activation (Widdel and Rabus, 2001;Wilkes et al, 2002). Anaerobic degradation of n-alkanes, branched alkanes and pristane was detected in enriched bacterial communities that reduce nitrates (Bregnard et al, 1997;Rabus et al, 1999;Ehrenreich et al, 2000) and sulfates (Aeckersberg et al, 1991;Rueter et al, 1994;So and Young, 1999). Anaerobic biodegradation of long chain n-alkanes to form methane and CO 2 by methanogenesis (Zengler et al, 1999;Anderson and Lovley, 2000) was demonstrated.…”
Section: O2 Classmentioning
confidence: 99%
“…n-Alkanes were anaerobically oxidized in pure cultures using sulfate (2,3,41,43) or nitrate (18) as the electron acceptor or in enrichment cultures with sulfate (16) or nitrate (13,39). Also, anaerobic conversion of long-chain n-alkanes to methane and CO 2 in associations of enriched bacteria and archaea was demonstrated (4,55).…”
mentioning
confidence: 99%